Elaboration of learning cycle 5E model and PJBL based on creative products and fun entrepreneurship through shutterstock application - Moningka, Yudha; Aprilia, Nani; Isnaeni, Bekti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
PKK subject is a lesson about ethics, values, skills and attitudes in facing the challenges of life to obtain opportunities in various risks faced. The implementation of